Glucose‐Responsive Insulin Delivery: Microneedle‐Array Patch Fabricated with Enzyme‐Free Polymeric Components Capable of On‐Demand Insulin Delivery (Adv. Funct. Mater. 7/2019). (12th February 2019) - Chen, Siyuan; Matsumoto, Hiroko; Moro‐oka, Yuki; Tanaka, Miyako; Miyahara, Yuji; Suganami, Takayoshi; Matsumoto, Akira
Abstract : In article number1807369, Akira Matsumoto and co‐workers report an electronics‐free, enzyme‐free, and nanoparticle‐free smart artificial on‐skin pancreas, which is a hybrid microneedle‐array patch fabricated with a glucose‐sensitive boronate‐hydrogel and biocompatible silk fibroin semi‐interpenetrating network. This microneedles‐array patch could mimic the functionality of the pancreas and provide on‐demand insulin delivery in a safe, painless, and convenient way.